Microsoft excel functions and formulas : With excel 2019 / Office 365 / Bernd Held; Brian Moriarty; Theodor Richardson - Held, Bernd
In this completely updated edition covering Excel 2019, previous versions, and Office 365, Microsoft Excel Functions & Formulas 5/E demonstrates the secrets of Excel through the use of practical and useful examples in a quick reference format. Easy to use and equipped with a variety of functions, Microsoft Excel is the tool of choice when it comes to crunching numbers, building charts, and analyzing tables. The book’s extensive examples and added video tutorials make it an excellent resource for all Excel users who want to understand, create, and apply formulas. Experienced users will also find Microsoft Excel Functions & Formulas 5/E an excellent reference for many of the program’s advanced formulas and functions. The text is easy to understand with numerous step-by-step instructions and the actual, ready to use, Excel screenshots of the input and output from the formulas. The book includes companion files with video tutorials, over 250 worksheet files of examples for numerous functions, formulas, and all the figures from the text(all companion files also available for downloading from the publisher by writing to info@merclearning.com).